Practical Principles of Palliative Care in Veterinary Oncology: Alleviating the Suffering of the Animal, Owner, and Veterinarian - Paz, Beatriz F. [UNESP]; Ferreira, Marília G. P. A.; Martins, Ketlyn R. [UNESP]; Uccella, Lucas [UNESP]; Barboza De Nardi, Andrigo [UNESP] (Wiley, 2024)
Background. Palliative care for pets is a developing area that encompasses animals with cancer and other chronic and degenerative diseases. Objectives. To elucidate the guiding principles of palliative care in veterinary oncology. Methods. This article was structured from an extensive literature review and addresses the growing need for improved palliative care in veterinary medicine. Methods of quality of life assessment in animals with cancer, owner education, and the importance of an interdisciplinary team approach are discussed. Results. Palliative care aims to improve the animal's quality of life, alleviating its physical, emotional, and social suffering. Through attentive communication, palliative care also seeks to alleviate owners suffering from the moment of diagnosis to mourning the patient's death. Conclusions. The importance of offering palliative care alongside anticancer techniques and treatments should not be underestimated and should ideally use a multidisciplinary team approach.